2010
DOI: 10.1637/8764-033109-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Water-Based Foam and Inert-Gas Mass Emergency Depopulation Methods

Abstract: Current control strategies for avian influenza (AI) and other highly contagious poultry diseases include surveillance, quarantine, depopulation, disposal, and decontamination. Selection of the best method of emergency mass depopulation involves maximizing human health and safety while minimizing disease spread and animal welfare concerns. Proper selection must ensure that the method is compatible with the species, age, housing type, and disposal options. No one single method is appropriate for all situations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The method used for culling impacts animal welfare (van den Berg and Houdart, 2008;Alphin et al, 2010).…”
Section: 31mentioning
confidence: 99%
“…The method used for culling impacts animal welfare (van den Berg and Houdart, 2008;Alphin et al, 2010).…”
Section: 31mentioning
confidence: 99%
“…Two leads were implanted in the complexus muscle just below the base of the skull for electromyography (EMG). The ducks were given 0.4 mg/kg of carprofen injection subcutaneously after the procedure and were then allowed to recover for 24 h. The surgical procedure was based on Kostal (1997, 2006) and Alphin et al (2010).…”
Section: General Procedures and Instrumentationmentioning
confidence: 99%
“…Previous studies compared the effectiveness of CO 2 gassing Alphin et al, 2010) and argon-carbon dioxide gassing (Alphin et al, 2010) to water-based foam for the depopulation of floor-reared poultry and found that the mentioned methods are comparable. There are physiological differences in the mechanisms causing death for foam and CO 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…EEG has been used to monitor brain activity of humans and a number of different species. EEG has been used in connection with animal welfare studies to determine the time to unconsciousness and brain death during euthanasia or depopulation (Alphin et al, 2010;Gerritzen et al, 2006;Raj, 1998). Radiotelemetery systems have been used to allow the real time measurement of heart rate, blood pressure, body temperature and telencephalic EEG to be used as an indicator of bird welfare parameters (Savory and Kostal, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of these two experiments was that an increase would be seen in the relative alpha or relative beta frequencies and a decrease would be seen in the relative delta or relative theta frequencies during the application of stressful stimuli. It was assumed that relative delta/theta would decrease during a stressful period because relative delta/theta tend to increase during unconsciousness , when an animal is not responding to stimuli (Lambooij et al, 2002;Lopes, 1983;Raj et al, 1992;Raj, 1998, Gerritzen et al, 2004Alphin et al, 2010). Plasma corticosterone levels were used in Experiment 2 as a standard measure of evaluating stress (Harvey et al, 1980;Klingbeil, 1985;de Boer et al, 1988) against which any changes seen in the relative frequency bands of the EEG were measured.…”
Section: Introductionmentioning
confidence: 99%